2008
DOI: 10.1007/s00125-008-1077-x
|View full text |Cite
|
Sign up to set email alerts
|

Is a nutritional therapeutic approach unsuitable for metabolically healthy but obese women?

Abstract: Metabolically healthy but obese postmenopausal women are a subset of obese individuals who do not show obesityrelated metabolic abnormalities such as insulin resistance, a pro-atherosclerotic lipid profile, a proinflammatory state and hypertension [1,2]. In longitudinal studies, this phenotype was associated with reduced risks of developing type 2 diabetes and cardiovascular disease [3].These 'fit-fat individuals' are of interest because they constitute a model that may provide insight into the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…These findings are in line with those showing that excess fat is involved in the generation of oxidative stress [30]. Even if it has been suggested that physical exercise rather than an energy-restricted diet could be recommended as an essential method for body weight reduction [31,32], in this work we showed that the protective benefit generated by HD treatment could be reinforced by regular moderate aerobic exercise. This benefit could to be related to an induction of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 78%
“…These findings are in line with those showing that excess fat is involved in the generation of oxidative stress [30]. Even if it has been suggested that physical exercise rather than an energy-restricted diet could be recommended as an essential method for body weight reduction [31,32], in this work we showed that the protective benefit generated by HD treatment could be reinforced by regular moderate aerobic exercise. This benefit could to be related to an induction of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 78%
“…All three studies showed an improvement in cardiovascular risk profile in OIR, but not in MHO, women, despite similar weight loss [8][9][10]. In view of these findings and the limited healthcare resources, the necessity and the benefit of a lifestyle intervention in MHO individuals has been questioned [11,12]. On the other hand, while OIR individuals clearly benefit from the lifestyle intervention [8][9][10], it is important to know whether this effect is sufficient to place them in a position where protection from obesity-related metabolic consequences is expected.…”
Section: Introductionmentioning
confidence: 99%
“…It has indeed been suggested that weight loss in postmenopausal MHO women may be unnecessary and paradoxically harmful given the favorable metabolic profile of these individuals [18]. Whether these findings also apply to premenopausal obese women remains to be investigated [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Intervention studies investigating the effect of weight loss on cardiometabolic risk factors in MHO individuals have yielded contradictory results, and the question of whether weight loss is also a priority in MHO individuals is still under debate [2,14]. Evangelou et al [15] reported that MHO individuals showed lower reduction in their body weight after a 3-month low-fat diet plus weight-reducing drugs compared with a 6 years older group of obese and overweight patients with metabolic syndrome, whereas Kantartzis et al [16] showed similar body weight reductions in both MHO individuals and an obese group of men and women with insulin resistance after a 9-month lifestyle intervention program.…”
Section: Introductionmentioning
confidence: 99%